Physics in Resources Recycling: Jig Separation of Plastics - Alorro, Richard; Tsunekawa, Masami (Philippine Physics Society, 2009)
Recycling has gained attention nowadays due to the increasing awareness in sustainable development. The recycling of waste plastics has become one of the priorities because of the rising consumption and generation of plastic wastes from different sectors of the society. Waste plastics are composed of a mixture of different types of plastics and need to be separated before they can be recycled. Several techniques were investigated or developed to separate plastics and one of them is jig separation. Jig separation is based on the displacement of particles in a bed fluidized by the pulsation of the fluid in a vertical plane so as to produce stratification. The principles behind jigging are governed by physics, particularly the motion of particles in fluid. This paper presents the theories proposed to effect particle separation by jigging. Studies on the application of jigging to separate different kinds of plastics were reviewed. It can be concluded that jig separation can be applied for plastic separation and recycling. However, more research and development effort is required before a commercial scale application can be established.